Perspective paper about the joint EANM/SNMMI/ESTRO practice recommendations for the use of 2-[18F]FDG-PET/CT external beam radiation treatment planning in lung cancer. (March 2022) - Vaz, Sofia C.; Adam, Judit A.; Delgado Bolton, Roberto C.; Vera, Pierre; van Elmpt, Wouter; Herrmann, Ken; Hicks, Rodney J.; Lievens, Yolande; Santos, Andrea; Schöder, Heiko; Dubray, Bernard; Visvikis, Dimitris; et al.
Abstract: In "Joint EANM/SNMMI/ESTRO Practice Recommendations for the Use of 2-[18F]FDG-PET/CT External Beam Radiation Treatment Planning in Lung Cancer V1.0" clinical indications for PET-CT in (non-)small cell lung cancer are highlighted and selective nodal irradiation is discussed. Additionally, concepts about target definition, target delineation and treatment evaluation are reviewed.